Association between dietary diversity, nutritional status, and academic performance of school-age children in Southeast Ethiopia using structural equation modelling - Girma Beressa; Abera Biratu; Bikila Lencha; Biniyam Sahiledengle; Demisu Zenbaba; Desalegn Bekele; Yohannes Tekalegn; Kenenisa Beressa (BMC, 2024)
Abstract Background Undernutrition, manifested as stunting and/or thinness, is a major public health concern in low-income countries, including Ethiopia. Factors such as sociodemographic, economic, and dietary status influence children's academic achievement. This study aimed to assess the association between dietary diversity, nutritional status, and academic performance of school-age children in pastoral communities in Southeast Ethiopia. Methods A school-based cross-sectional study was conducted among 395 randomly selected school-age children. A multistage sampling followed by systematic random sampling was used to collect the data. Students' academic performance (AP) was evaluated by computing two-semester average grade scores of the 2016/17 academic year in all disciplines using the school record. A pre-tested, interviewer-administered, structured questionnaire was used to collect the data. To assess nutritional status, the z scores of height for age (HAZ) and BMI for age (BAZ) were employed according to WHO's new reference values. The WHO Anthroplus software was used to generate nutritional indices. A structural equation model (SEM) was used to examine the direct, indirect, and total effects of the dietary diversity score (DDS), HAZ score, and BAZ score on AP. The beta coefficient (β) along with the confidence interval (CI) were used to estimate the strength of the association. Results The prevalence of stunting and thinness was 26.6% (95% CI: 21.8, 31.4%) and 28.9% (95% CI: 24.3, 33.2%), respectively. The proportion of dietary diversity (DD) among school-age children was 40% (95% CI: 35.7, 45.3%) low DD and 60% (95% CI: 54.7, 64.3%) adequate DD. The SEM revealed that a unit increment in the child's DDS (unstandardised β = 0.130, 95% CI: 0.049 to 0.211) did have direct and total effects on the HAZ score. However, HAZ score, BAZ score, and DDS did not have direct, indirect, or total effects on AP. Similarly, DDS did not have direct or total effects on the BAZ score. Conclusion The academic performance (AP) was low among these school-age children, and the prevalence of stunting and thinness was high. Thus, nutrition interventions on dietary diversity for school-age children would be crucial interventions for increasing academic achievement.